Sepsis-related hospital admissions and ambient air pollution: a time series analysis in 6 Chinese cities - Yu Wang; Zhen Liu; Lian Yang; Jiushun Zhou; Jia Li; Hai Lun Liao; Xing Jun Tian (BMC, 2021)
Abstract Background Some prevalent but rarely studied causes of hospital admissions, such as sepsis is still unknown whether affected by air pollution. Methods We used time-series regression within generalized additive models to estimate the effect of air pollutant level on the sepsis-related hospital admissions, for the years 2017-18, using data from six cities in Sichuan, China. Potential effect modifications by age and sex were also explored. The effects of air pollutant on hospital stays for sepsis were also quantified. Results Positive associations between short-term exposure to NO2 and O3 and risk of sepsis-related hospital admissions and stays were found. Each 10 μg/m3 increase in short-term NO2 at lag 03 and O3 at lag 4 was associated with an increase of 2.76% (95% CI: 0.67, 4.84%) and 0.64% (95% CI: 0.14, 1.14%) hospital admissions, respectively. An increase of 0.72% (95% CI: 0.05, 1.40%) hospital stay was associated with 10 μg/m3 increase in O3 concentration at lag 4. Besides, the adverse effect of exposure to NO2 was more significant in males and population aged less than 14 years; while more significant in females and population aged 14 ~ 65 and over 65 years for exposure to O3. These associations remained stable after the adjustment of other air pollutants.8. Conclusion Exposure to ambient NO2 and O3 may cause substantial sepsis hospitalizations, and hospital stays in Sichuan, China. These associations were different in subgroup by age and sex.